Antibacterial Analysis of Human Amniotic Membrane Against Streptococcus Mutants, Streptococcus Sobrinus, and Enterococcus Faecalis - Yusoff, Mohamad Ezany; Hamdan, Ruhil Hayati; Taib, Haslina; Peng, Tan Li; Mohamed, Maizan; Shaari, Rumaizi; Awang Nawi, Mohamad Arif (Journal of Dentistry Indonesia, 2025)
Objectives: The human amniotic membrane (HAM) is a promising scaffold for oral applications due to its antimicrobial properties, which help protect against bacterial degradation. However, evidence of its activity against oral bacteria remains limited. Thus, this study aimed to evaluate the antibacterial activity of the HAM against selected Gram-positive oral bacteria, namely, Streptococcus mutans (S. mutans), Streptococcus sobrinus (S. sobrinus), and Enterococcus faecalis (E. faecalis). Methods: HAM in 1 cm2-pieces was inoculated with bacterial suspensions and incubated at 37 °C in 5% carbon dioxide (CO2) for 48 hours to evaluate its inhibition activity. Tetracycline-30 and 0.2% Chlorhexidine served as the positive controls, while phosphate-buffered saline (PBS) was used as the negative control. Swabs from the inhibition zone were re-cultured on Mueller-Hinton agar to test for the bacteriostatic and bactericidal effects of the HAM. Results: HAM inhibited the growth of S. mutans and S. sobrinus but showed no activity against E. faecalis. It also exhibited bactericidal effects against both the Streptococcus species. A statistical analysis revealed a significantly smaller inhibition zone for the HAM compared with the positive controls, while there was no significant difference compared to the PBS. Conclusion: The human amniotic membrane (HAM) demonstrated antibacterial and bactericidal activity against the selected Streptococcus species, but not E. faecalis. The antibacterial properties of HAM against other oral pathogens require further studies to explore its potential as an oral scaffold.